2015
DOI: 10.1002/pola.27946
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanistic investigation of epoxy-anhydride compositions cured with quaternary phosphonium salts as accelerators

Abstract: Mechanism and curing kinetics of bisphenol A epoxy resin-iso-methyltetrahydrophthalic anhydride compositions using quaternary phosphonium salts as accelerators were investigated by differential scanning calorimetry (DSC) and electrospray mass-spectrometry (ESI-MS). The DSC method was applied to investigate curing kinetics and apparent activation energy values for the overall curing process. The DSC results showed that some of the phosphonium salts lead to a lower activation energy, that means they are more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Many strategies have been executed to develop one-component epoxy resins with workable pot life and viscosity profiles [ 18 ]. One of the approaches is to take advantage of the dissolubility difference between the epoxy and amine hardener [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been executed to develop one-component epoxy resins with workable pot life and viscosity profiles [ 18 ]. One of the approaches is to take advantage of the dissolubility difference between the epoxy and amine hardener [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another work reported by our group, the addition of 1‐butyl‐3‐methyl imidazolium‐tetrafluorborate (bmim.BF 4 ) (1–5 phr – part per hundred part of resin) resulted in a decrease in the curing rate of EP/anhydride but an increasing in the curing process of EP/4,4′‐methylene‐bis‐ (3‐chloro‐2,6‐diethyl‐aniline (MCDEA), an aromatic amine 15 . Amirova et al also reported the effectiveness of some quaternary phosphonium salts as accelerators for the curing process of EP/anhydride system 21 . According to the authors, the phosphonium salts activate the anhydride by electrophilic attack.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Buchmeiser et al proposed innovative approach by using protected N -heterocyclic carbenes as latent organocatalysts for the low-temperature curing of epoxy:anhydride thermosets [ 27 , 28 ]. Moreover, it is possible to obtain a one-component mixture with an increased pot-life with epoxy/anhydride systems [ 29 ] Anhydrides are potentially bio-based [ 30 , 31 ] and can provide the thermosets with tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of curing of epoxy with anhydrides differs from amines since it exhibits initiation, propagation and termination steps similar to a ring-opening polymerization. Conflicting initiation mechanisms have been reported, but most of them agree on the formation of a zwitterion [ 29 , 32 , 33 , 34 ]. For Park et al [ 32 ], it occurs via the ring-opening of the epoxide by the catalyst ( Scheme 2 ), while the nucleophilic attack can similarly occur on the anhydride according to Amirova et al [ 29 ] ( Scheme 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation